THE INSERTION OF EDUCATIVE SOFTWARE IN THE EDUCATION OF YOUNG AND ADULTS A SOCIAL IMPACT AND THE METHOD BIOECOLÓGICO DE BRONFENBRENNER (Fiep Bulletin - online, 2013)
The present study it has for objective to describe the origin and the development of a project on Alfabetização de Jovens and Adultos and basically to stand out that this proposal educational has the Program PROTECTS - Technological Program for Young e Adult, as main tool, where the professor is facilitador and the pupil, an active collaborator. Before however, it is important to stand out that this project had as base the comment, the experience and the reality of the community, feeding itself of the vision that we project in the future of the education, in which this reality if presents transformed. In the education contemporary, the pedagogia is signaling consistent and práxis paradigms taking care of to the necessities of the current world, where the citizenship, the support, the potentiality, the globalization, the transdisciplinaridade, the dialogilidade and the individuality will have to be valued. The viability and the efficiency of this pedagogical project, associated to the relevance of the subject, allow to the intermeshing possibility, thus establishing an interface between the pedagogical aspects and ecological the theoretical conception on the human development, in search of better forms to teach and to learn, thus promoting, the improvement of the quality of education and the development of the individual as a whole. The present project has as referencial theoretician of analysis and quarrel, the Bioecologica Theory of the Human Development, developed for Urie Bronfenbrenner. This study one consists of a methodology that takes care of to the necessities of the modern life, through a didactic tool with dynamic resource that, stimulating the pupil, results in physical and mannering changes, thus favoring the formation integral of the individual.
Keywords: Illiteracy; Technology; Bioecológica Theory of the Human Development